Diacoptical Z–Y Mathematical Model for Correction of Steady-State Mode of Large Electric Power System - K. V. Khachatrian (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper proposes a new method for construction of a Z–Y diacoptical mathematical model for correction of steady-state electric power system mode in the case when a state of a passive part of the electric power network is assigned in the Z–Y form.